Long-Term Effects of Rainfall Shocks on Foundational Cognitive Skills: Evidence from Peru - Nicolas Pazos; Marta Favara; Alan Sanchez; Douglas Scott; Jere R. Behrman (Institute of Labor Economics (IZA), 2023)
Global warming is changing precipitation patterns, harming communities strongly tied to agricultural production, particularly in low-and-middle income countries (LMICs). Whilst the long-term effects of being exposed to rainfall shocks early in life on school achievement tests are well-established, there is little population-based evidence from LMICs on the mechanisms through which these shocks operate. This paper analyses the effects of early exposure to rainfall shocks on four foundational cognitive skills (FCSs), including executive functions (EF) that have been found to be key predictors of educational success. These skills were measured via a series of tablet-based tasks administered in Peru as part of the Young Lives longitudinal study (YLS). We combine the YLS data with gridded data on monthly precipitation to generate monthly, community-level rainfall estimates. The key identification strategy relies on temporary climatic shocks being uncorrelated with other latent determinants of FCS development. Our results show significant negative effects of early life exposure to rainfall shocks on EF. We also find evidence of rainfall shocks decreasing households' abilities to invest in human capital, which may affect both FCS and domain-specific test scores. Interestingly, social policies providing affected households with additional resources partially offset the effects of the rainfall shocks.
Keywords: J24; Q54; I24; I14; 330; skills formation; human capital; rainfall; Peru; early childhood